Crystal and magnetic structure of antiferromagnetic Mn2PtPd. (8th June 2018) - Kumar, Vivek; Reehuis, Manfred; Hoser, Andreas; Adler, Peter; Felser, Claudia
Abstract: We have investigated the crystal and magnetic structure of Mn2 PtPd alloy using powder x-ray and neutron diffraction experiments. This compound is believed to belong to the Heusler family having crystal symmetry I 4/ mmm (TiAl3 -type). However, in this work we found that the Pd and Pt atoms are disordered and thus Mn2 PtPd crystallizes in the L 10 structure having P 4/ mmm symmetry (CuAu-I type) like MnPt and MnPd binary alloys. The lattice constants are a   =  2.86 Å and c   =  3.62 Å at room temperature. Mn2 PtPd has a collinear antiferromagnetic spin structure below the Néel temperature T N   =  866 K, where Mn moments of ~4 µ B lie in the ab -plane. We observed a strong change in the lattice parameters near T N . The sample exhibits metallic behaviour, where electrical resistivity and carrier concentration are of the order of 10 −5 Ω cm and 10 21 cm −3, respectively.